Morphology of the vaginal complex in the white-eared opossum (Didelphis albiventris): Gross anatomy and light microscopy - Schimming, Bruno C. [UNESP]; Cesario, Maria D. [UNESP]; Matheus, Selma M. M. [UNESP] (Wiley, 2018)
Opossums, the largest marsupials found in Brazil, are animals of great interest due to their commonality in large urban centres and their frequent use as laboratory animals. Thus, this study was designed to describe the vaginal complex in ten female opossums by gross anatomy and light microscopy. The vaginal complex comprises two lateral vaginae, a vaginal cul-de-sac and a urogenital sinus. No marked morphological contrast of the vaginal complex was observed in the proestrus and metestrus phases of the females studied. The epithelium lining of cul-de-sac was simple columnar and folded. The lateral vagina was lined by a stratified squamous epithelium that was keratinised in its cranial portion and nonkeratinised in the caudal region. The urogenital sinus was also lined by a stratified squamous epithelium. The morphology of vaginal complex of white-eared opossum is similar to those reported for other marsupials, showing similar histological features.